Cochlear Implant Electrode Effect on Sound Energy Transfer Within the Cochlea During Acoustic Stimulation. Issue 9 (October 2015) - Greene, Nathaniel T.; Mattingly, Jameson K.; Jenkins, Herman A.; Tollin, Daniel J.; Easter, James R.; Cass, Stephen P.
Abstract : Hypothesis: Cochlear implants (CIs) designed for hearing preservation will not alter mechanical properties of the middle and inner ears as measured by intracochlear pressure (PIC ) and stapes velocity (Vstap ). Background: CIs designed to provide combined electroacoustic stimulation are now available. To maintain functional acoustic hearing, it is important to know if a CI electrode can alter middle or inner ear mechanics because any alteration could contribute to elevated low-frequency thresholds in electroacoustic stimulation patients. Methods: Seven human cadaveric temporal bones were prepared, and pure-tone stimuli from 120 Hz to 10 kHz were presented at a range of intensities up to 110 dB sound pressure level. P IC in the scala vestibuli ( P SV ) and tympani ( P ST ) were measured with fiber-optic pressure sensors concurrently with V Stap using laser Doppler vibrometry. Five CI electrodes from two different manufacturers with varying dimensions were inserted via a round window approach at six different depths (16–25 mm). Results: The responses of P IC and V Stap to acoustic stimulation were assessed as a function of stimulus frequency, normalized to sound pressure level in the external auditory canal, at baseline and electrode-inserted conditions. Responses measured with electrodes inserted were generally within approximately 5 dB of baseline, indicating little effect of CI electrode insertion on P IC and V Stap . Overall, mean differences across conditions were small for all responses, and no substantial differences were consistently visible across electrode types. Conclusion: Results suggest that the influence of a CI electrode on middle and inner ear mechanics is minimal despite variation in electrode lengths and configurations.